The effect of steroid administration on fetal diaphragm function - Fatma Ozdemir; Gokhan Acmaz; Yusuf Madendag; Ilknur Col Madendag; Iptisam Ipek Muderris (BMC, 2022)
Abstract Background Antenatal steroid administrations lead to not only accelerated lung maturation, improved blood gas measurements but also lung dynamics and lung compliance. This study aimed to investigate structural and functional changes in diaphragm after antenatal steroid administration. Methods The 79 volunteers were divided into 2 groups according to presence of preterm delivery. Betamethasone (CelestoneR) 12 mg intramuscularly was routinely administered to pregnancies complicated with preterm delivery between 28th -34th weeks of gestation. Same dose was repeated 24 h later. In all patients, diaphragm thickness, diaphragmatic excursion and costophrenic angle were measured in both the inspirium and expirium stage of respiration. This is an observational cross-sectional study. Results Diaphragm thickness, diaphragmatic excursion and diaphragm thickening fraction parameters were improved but costophrenic angle was not different 7 days after steroid administration. Diaphragm thickness, diaphragmatic excursion and costophrenic angle changes during inspiration and expiration stage after 7 days of betamethasone treatment reflects the effect of steroid administration on diaphragm muscle. Comparisons of the differences that occur after steroid rescue protocol were done by subtracting the diaphragm thickness, diaphragmatic excursion and costophrenic angle parameters before the treatment from the diaphragm thickness, diaphragmatic excursion and costophrenic angle parameters 7 days after steroid treatment respectively. Conclusion Diaphragm became more mobile in patients with preterm labor, 7 days after steroid administration. This situation reflects positive effect of steroid administration on diaphragm function.